2014
DOI: 10.1177/1524838014537908
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Maltreatment and Educational Outcomes

Abstract: Children (0-18 years) with maltreatment histories are vulnerable to experiencing difficulties across multiple domains of functioning, including educational outcomes that encompass not only academic achievement but also mental well-being. The current literature review adopted Slade and Wissow's model to examine (1) the link between childhood maltreatment and academic achievement, (2) the link between childhood maltreatment and mental health outcomes (i.e., emotional and behavioral difficulties), and (3) the bid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
144
2
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(166 citation statements)
references
References 54 publications
11
144
2
9
Order By: Relevance
“…Results showed that individuals with a history of grade repetition experienced a greater number of stressful life events than those without such a history. Similar results have been reported by other studies in the literature (Brancalhone, Fogo & Williams, 2004;Romano et al, 2015;Sbaraini & Schermann, 2008). Sbaraini and Schermann (2008) found that children who experienced a high number of stressful events by age 10 were also more likely to have repeated grades in school.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Results showed that individuals with a history of grade repetition experienced a greater number of stressful life events than those without such a history. Similar results have been reported by other studies in the literature (Brancalhone, Fogo & Williams, 2004;Romano et al, 2015;Sbaraini & Schermann, 2008). Sbaraini and Schermann (2008) found that children who experienced a high number of stressful events by age 10 were also more likely to have repeated grades in school.…”
Section: Discussionsupporting
confidence: 89%
“…Stressful life events in childhood have been shown to have an important impact on cognitive and academic performance (Fishbein et al, 2009;Spann et al, 2012;Weidmana, Augustineb, Murayamac, & Elliote, 2015) and to influence learning abilities (Romano, Babchishin, Marquis, & Fréchette, 2015;Sbaraini & Schermann, 2008). A study by Pereira, Santos, and Williams (2009) found that children exposed to maltreatment had worse school performance than non-exposed peers in the same grade, and of the same age and gender.…”
Section: Introductionmentioning
confidence: 99%
“…Another limited set of papers (N = 2) utilized the later concepts of proximal processes and the PPCT model. Two of the reviewed articles (Mutumba and Harper 2015;Romano et al 2015) used concepts of Bronfenbrenner's theory (at least partly) in conjunction with other theoretical frameworks, while the others were based solely on concepts from Bronfenbrenner's theory. Table 2 summarizes how the theory has been utilized within these three identified groups of articles with regard to the purpose of using Bronfenbrenner's theory; study designs; concepts utilized; main results; implications for public mental health policy and interventions; and strengths and weaknesses for guiding public mental health policy and practice.…”
Section: Different Uses Of Bronfenbrenner's Theory In Mental Health Rmentioning
confidence: 99%
“…Likewise, Behnke et al (2011) were able to detect how the association between factors at different ecological levels and depressive symptoms differed for girls and boys. Equally, Romano et al (2015), in their review of the complex relationship between childhood maltreatment and later academic achievement and mental health, found that the negative consequences of childhood maltreatment seemed to be greater for boys than girls. They also found that some forms of maltreatment (early in life, multiple, neglect) seemed to be especially harmful for academic achievements.…”
Section: Studies Utilizing Ecological Systems Concepts By Consideringmentioning
confidence: 99%
See 1 more Smart Citation